Controlling the pasting, rheological, gel, and structural properties of corn starch by incorporation of debranched waxy corn starch. (February 2022) - Xiao, Wenhao; Shen, Mingyue; Ren, Yanming; Wen, Huiliang; Li, Jinwang; Rong, Liyuan; Liu, Wenmeng; Xie, Jianhua
Abstract: This study aimed to investigate the effects of debranched waxy corn starch (DWCS) on the pasting, rheological, gelatinization, and microstructural properties of native corn starch (NCS). Pasting properties showed a linear decrease (R 2  > 0.98) in peak, trough, breakdown, setback and final viscosity after replacing NCS with DWCS. However, the stability ratio, peak time and peak temperature linearly increased. This could be explained that DWCS competed with NCS for water, thereby inhibiting NCS gelatinization process. The introduction of DWCS decreased the consistency coefficient ( K ) while increased the flow behavior index ( n ) of NCS gels. The gel hardness of NCS gels decreased linearly ( R 2  = 0.98) with increasing DWCS fraction, while the adhesiveness gradually increased. Moreover, DWCS could effectively reduce the values of short-range ordered degree and relative crystallinity. Scanning electron microscopy revealed that a more disordered structure was appeared when DWCS was added to the NCS gel. Overall, this study reveals that DWCS is an effective agent for altering and regulation the physicochemical and structural properties of NCS. Graphical abstract: Image 1 Highlights: Normal corn starch (NCS)-debranched waxy corn starch (DWCS) gels were prepared. DWCS linearly increased the gel stability ratio while reduced the pasting viscosity. DWCS reduced gel hardness while increased adhesiveness of NCS-DWCS gels. DWCS decreased short-range ordered structure and relative crystallinity of gels.